1988
DOI: 10.1071/bi9880357
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Lactating Ewes to Exogenous Growth Hormone: Short- and Long-term Effects on Productivity and Tissue Utilization of Key Metabolites

Abstract: Responses to daily injections of bovine growth hormone (GH, 0·15 mg kg-1 liveweight), beginning on day 10 of lactation, were measured in lactating ewes. Milk yields of GH-treated ewes increased soon after commencement of injections and continued to increase for some 25 days before reaching plateau levels. By comparison, yields of ewes injected with excipient (controls) decreased over the experiment. There was a tendency for contents of milk fat to be higher and milk protein to be lower for GH-treated than for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 18 publications
4
13
0
Order By: Relevance
“…Several investigations have shown that mammary gland glucose uptake depends on an increase in arterial plasma glucose concentration (Fullerton et al 1989;Sandles et al 1988), whereas other works have demonstrated no difference (McDowell et al 1987;Mepham 1993). The results of the present study support the latter observation in both cooled and non-cooled animals.…”
Section: Discussionsupporting
confidence: 94%
“…Several investigations have shown that mammary gland glucose uptake depends on an increase in arterial plasma glucose concentration (Fullerton et al 1989;Sandles et al 1988), whereas other works have demonstrated no difference (McDowell et al 1987;Mepham 1993). The results of the present study support the latter observation in both cooled and non-cooled animals.…”
Section: Discussionsupporting
confidence: 94%
“…Whether the effects on IGF-I transport observed here for mammary tissue were due to insulin remains to be established, although increase in plasma insulin concentration is observed after GH treatment of lactating ruminants in positive energy balance (e.g. Sandles, Sun, D'Cruz et al 1988). Interaction between insulin and IGF to regulate tissue metabolism according to nutritional status is an attractive concept considering the con¬ trasting roles of insulin and GH in lipid, carbohydrate and nitrogen metabolism (Vernon, 1989).…”
Section: Discussionmentioning
confidence: 95%
“…The role of GH in late pregnancy and early parturition in several species has been identified as supportive of processes that facilitate milk synthesis by the mammary gland Sandles et al, 1988;. In this study, GH concentrations were similar in both hysterectomized and pregnant gihs from day 99 until parturition.…”
Section: Discussionsupporting
confidence: 52%
“…The part played by growth hormone (GH) when administered over short periods of time during late pregnancy and/or lactation has been reported in cattle (Peel et al, 1982;McDowell et al, 1987), sheep ; Sandles et al, 1988), rats and pigs . In all these studies, there is a consistent finding that GH alters nutrient utilization in muscle and mammary tissue in a manner that favors increased nutrient supply for milk synthesis.…”
Section: The Role Of Growth Hormone During Pregnancy and Lactationmentioning
confidence: 99%
See 1 more Smart Citation